Comparison of 4DMRI and 4DCT for the preoperative evaluation of patients with primary hyperparathyroidism. Issue 138 (May 2021) - Murugan, Narasimman; Kandasamy, Devasenathipathy; Sharma, Raju; Goyal, Ankur; Gupta, Arun Kumar; Tandon, Nikhil; Gupta, Nandita; Goswami, Ravinder; Vurthaluru, Seenu; Damle, Nishikant; Agrawal, Shipra
Abstract: Background: Minimally invasive parathyroid surgery is the standard of care in patients with Primary Hyperparathyroidism (PHPT) which requires accurate preoperative localization. Of all the available imaging modalities, 4DCT is considered the best modality for localization, however it entails the risk of ionizing radiation. To circumvent this 4DMRI was evaluated for parathyroid lesion localization. Purpose: To evaluate and compare the accuracy of 4DCT and 4DMRI in the localization of parathyroid Lesions. Materials and methods: In this ethically approved observational diagnostic study, 135 patients (age range: 10–75 years, male: female ratio - 1:2.1) with clinically and biochemically suspected PHPT were recruited. Of these, 56 patients underwent both 4DCT and 4DMRI. Six patients with positive imaging who didn't undergo surgery were excluded. A total of 50 patients with 61 proven parathyroid lesions were included for analysis. 48 patients had surgical and histopathological findings for the confirmation of imaging findings. Results: Both 4DCT and 4DMRI correctly detected 59/61 lesions in 48 patients. There was one false positive and two true negatives. In addition, 2 (3.22 %) lesions which were not detected by 4DCT and 4DMRI were found on surgery. The sensitivity of both 4DCT and 4DMRI was 96.7 %; specificity was 66.6 % and accuracy was 95.2 %. Conclusion: 4DMRI and 4DCT had similar accuracy for the detection of parathyroid lesions. However, 4DMRI has the advantage of lack of exposure to ionizing radiation, which can be beneficial in younger patients.